Physiological response, time-motion characteristics, and reproducibility of various speed-endurance drills in elite youth soccer players: small-sided games versus generic running - Ade, J. D.; Harley, J. A.; Bradley, P. (International Journal of Sports Physiology and Performance, 2014)
Purpose: To quantify the physiological responses, time-motion characteristics, and reproducibility of various speed-endurance-production (SEP) and speed-endurance-maintenance (SEM) drills. Methods: Sixteen elite male youth soccer players completed 4 drills: SEP 1 v 1 small-sided game (SSG), SEP running drill, SEM 2 v 2 SSG, and SEM running drill. Heart-rate response, blood lactate concentration, subjective rating of perceived exertion (RPE), and time-motion characteristics were recorded for each drill. Results: The SEP and SEM running drills elicited greater (P < .05) heart-rate responses, blood lactate concentrations, and RPE than the respective SSGs (ES 1.1-1.4 and 1.0-3.2). Players covered less (P < .01) total distance and high-intensity distance in the SEP and SEM SSGs than in the respective running drills (ES 6.0-22.1 and 3.0-18.4). Greater distances (P < .01) were covered in high to maximum acceleration/deceleration bands during the SEP and SEM SSGs than the respective running drills (ES 2.6-4.6 and 2.3-4.8). The SEP SSG and generic running protocols produced greater (P < .05) blood lactate concentrations than the respective SEM protocols (ES 1.2-1.7). Small to moderate test-retest variability was observed for heart-rate response (CV 0.9-1.9%), RPE (CV 2.9-5.7%), and blood lactate concentration (CV 9.9-14.4%); moderate to large test-retest variability was observed for high-intensity-running parameters (CV > 11.3%) and the majority of accelerations/deceleration distances (CV > 9.8%) for each drill. Conclusions: The data demonstrate the potential to tax the anaerobic energy system to different extents using speed-endurance SSGs and that SSGs elicit greater acceleration/deceleration load than generic running drills.